2020
DOI: 10.5812/ijp.101905
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Coronavirus NL63 Infection in Children with Upper Respiratory Infection by Real-Time PCR

Abstract: Background: Human coronavirus NL63 (HCoV-NL63) is a new respiratory virus associated with acute respiratory infection in children. Infection with this virus is usually accompanied by upper and lower infections of the respiratory tract in adults. Objectives: In a retrospective study, we investigated the incidence of coronavirus infection in children under the age of five years. Methods: We collected 138 specimens (nasal and throat swabs) from children less than five-years-old with acute respiratory infection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
3
2
1
Order By: Relevance
“…29 Since the first detection, the virus infection has been diagnosed in a few studies across the nation. 23,26 An investigation from Iran (before the pandemic) in a similar duration time as our study found HCoV-NL63 by using the same method as our method in nasal and throat swabs of 23.9% of cases (specified children aged <5 years) who had acute respiratory infections. 23 Given the differences between the inclusion criteria of this study compared with ours, different results could be explained.…”
Section: Demographics Prevalence and Seasonalitysupporting
confidence: 71%
See 3 more Smart Citations
“…29 Since the first detection, the virus infection has been diagnosed in a few studies across the nation. 23,26 An investigation from Iran (before the pandemic) in a similar duration time as our study found HCoV-NL63 by using the same method as our method in nasal and throat swabs of 23.9% of cases (specified children aged <5 years) who had acute respiratory infections. 23 Given the differences between the inclusion criteria of this study compared with ours, different results could be explained.…”
Section: Demographics Prevalence and Seasonalitysupporting
confidence: 71%
“…23,26 An investigation from Iran (before the pandemic) in a similar duration time as our study found HCoV-NL63 by using the same method as our method in nasal and throat swabs of 23.9% of cases (specified children aged <5 years) who had acute respiratory infections. 23 Given the differences between the inclusion criteria of this study compared with ours, different results could be explained. In addition to this study, there were some pieces of evidence from different countries with a lower detection rate (for instance, 1.2% in Japan, 30 2.1% in Australia, 31 and 2.5% in Canada 32 ), regarding the virus infection.…”
Section: Demographics Prevalence and Seasonalitysupporting
confidence: 71%
See 2 more Smart Citations
“…Seven found human coronaviruses cause aggressive or mild diseases. HCoV-229E, HCoV-OC43, HCoV-NL63, and HCoV-HKU1 create self-limiting respiratory diseases while SARS-CoV and MERS-CoV have a mortality rate of almost 10% and 40%, respectively [13,14]. SARS-CoV-2 is the latest species of coronaviruses causing another severe acute respiratory syndrome and makes a clade in the subgenus of sarbecovirus [15].…”
Section: The Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)mentioning
confidence: 99%